Expert System for Early Diagnosis of Diseases in Pet Cats Using the Forward Chaining Method - Suwinarno Nadjamuddin (Peneliti.net, 2023)
Cats are one of the animals that are popular and liked by the public. However, when their pet cat is sick, many cat owners are confused in finding information about the initial treatment, technical handling of the disease and the right medicine for the disease their cat is suffering from, so many cat owners give natural treatment. Therefore, the author creates an expert system that can assist cat owners in dealing with sick cats by using the forward chaining based on applicable rules according to the decision of an expert. This expert system can produce information on the initial diagnosis of a disease as well as initial solutions that can be carried out by cat owners in the technical handling of diseases suffered by their cats.